Physiotherapy Management in Individual with Spastic Stroke Hemiparesis Sinistra: A Case Report - Rosada, Amrina; Efendi, Elif Nur; Perdana, Surya Saputro (Academic Physiotherapy Conference Proceeding, 2022)
Introduction: Stroke is a functional brain disorder in the form of nerve paralysis caused by blood vessel diseases such as bleeding (ischemic) and busted blood vessels (hemorrhagic) in one part of the brain leading to blood flow reduction, brain cells death, and even brain-damage. In clinical appearance, a stroke will cause spasticity and reduction of muscle power and balance as the consequence of brain function degradation. Post-stroke patients with left hemiparesis who undergo stroke disorder because of hypotension should get appropriate medication, such as physiotherapy management.Case presentation: The subject in this study is a 50-year-old woman, 150 cm in height and 65 kg in weight, who works as a merchant. The patient complained about the stiffness and difficulty in moving the left side of her body since she was hospitalized. The first impression is that the patient was unable to walk and use a walking device. The hand looked clawed, the foot seemed to drop, and the skin of the left side looked drier compared to the other side. Currently, the patient is undergoing a physiotherapy program at Magetan Physiotherapy Clinic thrice a week. The items assessed in this study are muscle power, spasticity, balance for fall risk, range of motion and activity of daily living.Management and Outcome: The intervention in this case study is physiotherapy programs such as the bobath technique, tactile stimulation, pelvic tilting, mirror therapy, and infrared thrice a week for three weeks. The final evaluation showed muscle power improvement on the left side of the body, improving from 2 to 3; spasticity reduction, proven with an Ashworth scale from 1+ to 1; the activity of daily living ability improved to 60, interpreted as the patient only need minimum help; the balance function also showed minimum risk fall. Meanwhile, there was no significant change in ROM because of muscle weakness.Discussion: After three weeks research, the subjects showed improvement in left upper and lower extremity spasticity reduction, muscle power and balance enhancement.Conclusion: It can be concluded from the case that physiotherapy interventions such as bobath technique, pelvic tilting, tactile stimulation, mirror therapy, and infrared positively affect a post-stroke patient with left hemiparesis.